MENINGKATKAN KOMPETENSI PEDAGOGIK DENGAN PELAKSANAAN MICROTEACHING PADA MAHASISWA PGMI FAI UNIVERSITAS MUHAMMADIYAH SUMATERA BARAT - Vini Wela Septiana (Menara Ilmu, 2020)
This study aims to describe: Efforts to improve pedagogical competence by conducting microteaching of PGMI FAI students of Muhammadiyah University of West Sumatra, (2) The Role of Microteaching Supporting Lecturers in improving pedagogical competencies of PGMI FAI students at Muhammadiyah University, West Sumatra. This research is a descriptive qualitative research. The subjects in this study were students of PGMI FAI Muhammadiyah University of West Sumatra in 2018/2019 who had conducted microteaching in improving pedagogical competence. Data collection techniques used were in-depth interviews, observation, and documentation. The validity of the data in this study is triangulation (triangulation of sources and triangulation of techniques) and observationality. Data analysis techniques applied were data reduction, data display, and data verification. The conclusions in this study are: (1) there are various activities carried out in the implementation of microteaching as an effort to improve pedagogical competence of PGMI FAI students at Muhammadiyah University, West Sumatra. The implementation of these activities provides increased pedagogical competence of students which includes the ability to manage learning, understanding of students, learning design, learning implementation, use of learning technology, evaluation of learning outcomes, and student development. (2) The Role of Microteaching Supporting Lecturers in improving pedagogical competencies of PGMI FAI students at Muhammadiyah University, West Sumatra. This role includes the role of lecturers as educators, instructors, mentors, trainers, and developers in the implementation of microteaching programs. Keywords: competence, pedagogy, microteaching